AKTUALISASI NILAI BUDAYA SEI REEN DALAM ASPEK PENDIDIKAN PADA MASYARAKAT TONDANO - Tangkudung, Grace Filea Christy (HOLISTIK, Journal Of Social and Culture, 2016)
Indonesia country as a embodiment unity multi ethnic where there are many people coloring Indonesian. The movement of culture in each region the perceived. An Indonesian society pluralist with all the diversity local culture, produce the culture who was so beautiful, local wisdom culture and natural beauty owned be the unique. One nations in Indonesia is Minahasa, Minahasa ethnic itself is derived from North Sulawesi. Minahasa same as other ethnic has its own unique culture also has social institutions. The days of growing felt the process of shift the community and culture or usual known to social dynamics. Sei reen, which is a cultural value, should had a role as a stimulant, of the cultural play an important role in the process of forming and maintenance Minahasa identity. Education is a foundation early in a good life religious education, moral, and even knowledge. A tendency to shift education from the pivotal position viewed as an assumption on which getting attached to Tou Tondano. The cost of education is one of a whole host of reasons where the family as if are unable to continue the struggle for the study of children have pass out of high school. Sei reen has experienced shifts meaning and perform just symbolism course in reality life. Sei reen is contribution of life that drives others maintain imagery and Minahasa identity. Keywords: Minahasa identity, education, sei reen.AKTUALISASI NILAI BUDAYA SEI REEN DALAM ASPEK PENDIDIKAN PADA MASYARAKAT TONDANO